GPR snow depth survey over Svalbard Glaciers - Luks, Bartłomiej; Larose, Catherine; Spolaor, Andrea; Zoelly, Christian; Gallet, Jean-Charles (Zenodo, 2022)
Dataset contains results of GPR surveys of snowpack performed on five glaciers in Svalbard (Slakbreen, Longyearbreen, Maritbreen, Philipbreen andHoltedahlfonna). Surveys were performed in March - April 2008, with 800 MHz antenna (Mala ProEx system). Fieldwork was funded by the Svalbard Integrated Arctic Earth Observing SystemAccess project "Snow Observations in Svalabr (SOS)". Dataset consists of following unprocessed files: *.RAD - survey system and antenna control file *.COR - trace number, date, time and poistion *.MRK - reference markers *.RD3 - radarogram (clsed MALA ProEx format)